Strategi Implementasi Face Recognition sebagai Inovasi dalam Meningkatkan Akurasi Verifikasi Peserta Seleksi ASN - Nurul Jannah Lailatul Fitria; Mastina Maksin (Inovbook, 2022)
Governance towards good governance by applying the principles of bureaucratic reform. Bureaucratic reform is implemented in every sector, both as a form of service and implementation of the bureaucracy. Bureaucratic reform is also implemented to improve the quality of ASN. As in the procurement of CASN formation 2021. The government applies Face Recognition technology. This research focuses on implementing the technology in the form of bureaucratic reform. This research uses qualitative methods with an orientation to the latest case studies. Research with case studies is research on the latest phenomena and is examined in detail with a certain point of view. Research with qualitative methods focuses on data input related to understanding the material, mechanism, process of the phenomenon. So that it can be seen the mechanism for the application of face recognition technology in the procurement of CASN 2021 and is associated with the form of bureaucratic reform. In particular, the principles of efficient, effective, and fair bureaucratic reform. The orientation of CASN procurement is not only on quantity but quality to get ASN who are smart, capable, and of high quality, free of fraud and free of KKN.